Development of consensus-based international antimicrobial stewardship competencies for undergraduate nurse education. Issue 3 (November 2019) - Courtenay, M.; Castro-Sánchez, E.; Gallagher, R.; McEwen, J.; Bulabula, A.N.H.; Carre, Y.; Du Toit, B.; Figueiredo, R.M.; Gjerde, M.E.; Hamilton, N.; Jorgoni, L.; Ness, V.; et al.
Summary: Background: There is growing recognition by national and international policymakers of the contribution nurses make towards antimicrobial stewardship. Although undergraduate education provides an ideal opportunity to prepare nurses for antimicrobial stewardship roles and activities, only two-thirds of undergraduate nursing programmes incorporate any antimicrobial stewardship teaching and only 12% cover all the recommended antimicrobial stewardship principles. Nurses also report that they do not have a good knowledge of antibiotics, and many have not heard of the term antimicrobial stewardship. Aim: To provide international consensus on the antimicrobial stewardship competency descriptors appropriate for undergraduate nurse education. Methods: A modified Delphi approach comprising two online surveys delivered to an international panel of 15 individuals reflecting expertise in prescribing and medicines management in the education and practice of nurses; and antimicrobial stewardship. Data collection took place between February and March 2019. Findings: A total of 15 participants agreed to become members of the expert panel, of whom 13 (86%) completed round 1 questionnaire, and 13 (100%) completed round 2. Consensus was achieved, with consistently high levels of agreement across panel members, on six overarching competency domains and 63 descriptors, essential for antimicrobial stewardship practice. Conclusion: The competency descriptors should be used to direct undergraduate nurse education and the antimicrobial stewardship practices of qualified nurses (including those working in new roles such as Nursing Associates) due to the high levels of agreement reached on competency descriptors.